2008
DOI: 10.1038/sj.jid.5701258
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of MCP-1 Attenuates Cutaneous Ischemia–Reperfusion Injury in a Mouse Model of Pressure Ulcer

Abstract: The formation of pressure ulcers is dependent on multiple factors including ischemia-reperfusion (IR). This study assessed the mechanism of a previously reported murine model of cutaneous IR injury. Three cycles of IR (days 1-3) by external application of two magnetic plates were performed to induce pressure ulcer formation. Increased infiltration of neutrophils and macrophages, and augmented expression of proinflammatory cytokines and inducible nitric oxide synthase (iNOS), were observed during IR cycles. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 43 publications
(75 reference statements)
5
63
0
Order By: Relevance
“…Hair follicles had almost disappeared, in agreement findings by Şener et al (2006) and Saito et al (2008). Sebaceous glands were damaged and small in size.…”
Section: Microscopic Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…Hair follicles had almost disappeared, in agreement findings by Şener et al (2006) and Saito et al (2008). Sebaceous glands were damaged and small in size.…”
Section: Microscopic Findingssupporting
confidence: 90%
“…To produce pressure ulcers, the use of magnets has been reported in the literature (Peirce et al, 2000;Reid et al, 2004;Şener et al, 2006;Saito et al, 2008;Wassermann et al, 2009). However, the pressure in previous studies was either not measured or was not as accurate as in our experiment.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…3), we observed that relieving the pressure initially resulted in increased perfusion (reactive hyperaemia) 4,29 as the blood returned to the affected tissue. When blood returns to the ischaemic tissue, it produces reactive oxygen species and free radicals that can accelerate cell death 30,31 . In our model, 1 h of pressure produced mild reversible tissue damage, and 3 h of pressure produced more severe irreversible damage.…”
Section: Resultsmentioning
confidence: 99%
“…Third, chronic pressure ulcer features persistent chronic inflammation with leukocyte infiltration and release of proinflammatory cytokines [33,34]. Repetitive pressure and relief also lead to cutaneous ischemia-reperfusion injury, causing infiltration of inflammatory cells, deleterious cellular reactions and tissue damage by reactive free oxygen radicals [35]. Extensive evidence shows that chronic inflammation and infection outside the brain are associated with an increased risk of ischemic stroke via endothelial cell dysfunction, impaired fibrinolysis and activation of platelet aggregability altered by immune-mediated inflammatory cells and cytokines [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%